PENILE FRACTURE: EXPERIENCE AT AYUB TEACHING HOSPITAL - Khan, Raza Muhammad; Malik, Masud Akhtar; Jamil, Muhammad; Khan, Delawar; Shah, Iftikhar Hussain (Journal of Ayub Medical College Abbottabad, 2008)
Background: Penile fracture is a relatively rare traumatic rupture of the tunica albuginea of one or both corpora cavernosa of an erect penis. It is a real urological emergency which needs early assessment and surgical management. Methods: Twelve (12) cases of penile fracture were reviewed from July, 1997 to July, 2007 in the Department of Urology, Ayub Teaching Hospital Abbottabad. All cases presented with classical history of penile fracture and the diagnosis was made on the basis of history and clinical examination only. Results: All the patients underwent immediate surgical repair with well preserved potency and excellent overall results. Conclusion: Penile fracture has typical signs. Standard treatment consists of immediate surgical repair of penile fracture with a low incidence of late complications. Post op complications including urethral strictures and erectile dysfunction should be ruled out by regular follow-up. Keywords: Penile Fracture, Penis injuries